Practical guide for Java programmers - Brunner, Robert J. (Practical guide series (Amsterdam, Netherlands), 2003)
JavaServer Pages (JSP) is a technology for building dynamic web applications that can access databases and provide an interactive experience for users. It's a powerful technology with open source implementations (server and platform independent) for building enterprise Web applications. With JSP, existing business systems can be leveraged with minimal overhead, maintenance, and support. JSP: Practical Guide for Java Programmers is designed to cover the essentials of JSP including the basic JSP constructs and the relevant implicit objects as well as more advanced concepts such as incorporating.